Cross Cultural Examination of Students Attitudes and Intentions Towards AI in Higher Education - Long Wang ly; Kheterin Jhonly (Inovasi Analisis Data, 2025)
Objective: This paper is aimed at studying the attitudes and behavior of Chinese and international students towards the use of AI in higher education. It aims to gain insight into the cultural elements that shape students̶ perceptions of AI, while also examining the impact of these elements on students̶ intentions to embrace AI tools within their educational journeys.Methods: A purposive sampling approach was utilized to recruit students (both Chinese and international) from a Chinese university (n=800). Surveys were used to collect data, and the Technology Acceptance Model (TAM) was employed to evaluate the relationships between Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Towards Use (AU), and Behavioral Intention (BI) to adopt AI. We utilized reliability testing and descriptive statistics to ensure consistency and validity of the data.Results: Result shows relationships between PU, PEOU and, BI were significant positive with PU being a strong predictor of behavioral intentions of Chinese students. Compared to the international students, PU, PEOU, and BI exhibited a more even relationship. The study thus finds that culture plays an important role in the adoption of AI, with Chinese students placing greater emphasis on its perceived usefulness, as opposed to international students who are more focused on ease of use. These results are consistent with the Technology Acceptance Model and Hofstede’s cultural dimensions theory.Novelty: In addition, the doctoral dissertation adds to the research on AI adoption in higher education by studying the cultural differences of Chinese and international students. It expands the TAM with the inclusion of cultural factors as moderators respectively in students’ attitudes towards AI.Theory and Policy Implications: Such AI-based educational tools used by educational institutions and teachers in China should emphasize productivity and performance benefits The international students would benefit from user-friendly systems, the study suggested. AI uptake initiatives to suit cultural contexts, to ensure successful AI learning systems integration with education